Ensuring Confidentiality in the Detection and Investigation of the Crimes of Money Laundering - Khakberdiev Abdumurad (Rechtsidee, 2019)
This article analyzes tactics for combatting crimes related to money laundering based on international and national legislation as well as providing several recommendations on improving the system of combatting such crimes. Also, it determines, ensuring confidentiality in the detection and investigation of the crimes of money laundering. Finally, paper shows both outcomes and shortcomings of the points with some relevant examples.